Copper-Catalyzed One-Pot Multicomponent Reactions: Synthesis of 4-Arylsulfenyl Pyrazoles - H. Oliveira, Daniela; Alves, Diego; G. Jacob, Raquel; C. D. F. Xavier, Mauricio (Current Organic Synthesis, 2015)
We describe here a simple protocol for the synthesis of 4-(arylsulfenyl)-1H-pyrazoles by copper-catalyzed cyclocondensation and direct C–H bond sulfenylation reactions. The products were obtained in good yields by the reaction of a range of 1,3-diketones, arylhydrazines and arylthiols, using catalytic amount of CuI. This One-Pot Multicomponent protocol is an efficient method to synthesize new compounds with potential application in biological studies and material sciences.
Keywords: multicomponent